2021
DOI: 10.1097/gme.0000000000001884
|View full text |Cite
|
Sign up to set email alerts
|

The effects of estrogen deficiency and aging on myocardial deformation and motion in normotensive female rats

Abstract: Objective: Estrogen deficiency is associated with left ventricular (LV) dysfunction in postmenopausal women and ovariectomized rats. Whether the relationship between estrogen deficiency and LV dysfunction is independent of cardiovascular disease (CVD) risk factors remains uncertain. This study assessed the effects of short-term and long-term estrogen deficiency on cardiac structure and function using conventional and speckle tracking echocardiography, independent of traditional CVD risk factors.Methods: Female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…This study showed that ovariectomized rats had significantly decreased GLS but showed no significant difference after adjusting for BP and body mass. A lack of estrogen does not result in LV dysfunction, impaired myocardial deformation, or cardiac remodeling 29 . Our study also showed that age and hypertension were independent factors for reduced GLS in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that ovariectomized rats had significantly decreased GLS but showed no significant difference after adjusting for BP and body mass. A lack of estrogen does not result in LV dysfunction, impaired myocardial deformation, or cardiac remodeling 29 . Our study also showed that age and hypertension were independent factors for reduced GLS in multivariable analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies of women in different phases of the menstrual cycle as well as peri-, menopausal, and postmenopausal women, suggest that while sex hormones (especially E2 and FSH) regulate arterial stiffness, the effects are largely driven by age [ 92 ] . In support of this hypothesis, OVX did not cause independently cause cardiac remodeling and dysfunction in rats, but rather aging resulted in diastolic dysfunction and mild systolic impairment [ 93 ] . Together, these findings suggest that associations between hormones and cardiovascular function are likely different at different ages or reproductive stages.…”
Section: Mechanisms Of Sex Differences In Cardiac Agingmentioning
confidence: 99%
“…Исследования на животных с искусственной гипоэстрогенемией показали более быстрое развитие гипертрофии миокарда, а введение эстрогенов замедляло данный процесс [4]. Однако не все подобные исследования приходят к такому выводу [5]. Хотя исследования на животных открывают потенциальные механизмы ремоделирования сердечно-сосудистой системы, опосредованные половыми гормонами, эти модели часто используют изолированное изменение одного полового гормона и, следовательно, не являются оптимальным отражением сложных гормональных изменений у женщин в перименопаузе и постменопаузе.…”
Section: Introductionunclassified